LITERATURE REVIEW: PERBEDAAN KADAR HEMATOKRIT PADA ATLET DAN BUKAN ATLET - Adira Zahwa Ramadhina; Siti Kaidah; Huldani Huldani (Homeostasis, 2022)
In athletes, it is very important to maintain a good performance from start to finish, especially at certain times. The use of oxygen and blood flow will increase to meet the oxygen needs of the muscles during exercise. When there is increasing oxygen demand happens in the body, there will be stimulation of erythropoietin to produce red blood cells in the bone marrow, which is affect to the haematocrit value. The purpose of this literature review is to make a distinction about the difference in haematocrit levels in athletes and non-athletes. The reviewed articles were obtained through the Google Scholar and PubMed databases. The articles included are in English and Indonesian, published in 2011-2021. Different results were found between the studies appraised in this review, this could be due to differences in several factors such as duration, frequency, type of exercise, dehydration, gender, and nutritional intake